Anamorphs and strains from entomomogenous fungi Cordyceps on ant’s tropical rain forest from putumayense piedemonte - SANJUAN, TATIANA; AMAT, GERMÁN; HENAO, LUIS GUILLERMO (Revista Colombiana de Entomología, 2001)
Entomopathogenic fungí in Colombia have been covered from the biologic control perspective, and few data come from preserved ecosystems. This research studied Cordyceps, its anamorphs, and related strains, which parasitize ants in the tropical forest. In samplings carried out in the Colombian Amazonian foothill (450 - 600 m, during January and May of 1998) parasitized ants were collected in 100 sq. m (50 sq. m per period) in forest with different perturbation regimes. Lítter. scrubs and logs were sampled up to 2 m. The inoculates were obtained from the celoma of parasitized ants or stromata of Cordyceps, and cultured in different potato-dextrosa agar (PDA) and water media, and repeated to different media until sprouting of structures that allowed determination. The Cordyceps species found are C. kniphofioides var. ponerinum with its anamorph ffirsutella stilbelliformis, and C. australis in subfamily Ponerinae ants; C. lloydii var. binata and C. unilateralis in camponotus sp. (formicidae: Formicinae) ants; the last species was found related with three anamorphs: Hirsutella formicarum, Polycephalomyces sp. and Tilachlidium liberianum, two 1brrubiella species and three strains. In the laboratory we obtained the strains Verticillium lecanii and Paecilomyces sp. from sick ants into the same epizootic focus of C. unilateralis. The species, anamorphs, and strains of Cordyceps richness in the Putumayo foothill show the germplasm diversity of the tropical forests and its potential for biological control.